EVALUASI DAN PENGEMBANGAN OPERASI DAN PEMELIHARAAN SISTEM IRIGASI TADAH HUJAN DI KECAMATAN PULAU LAUT TIMUR KABUPATEN KOTABARU - Dina Heldita; Jeffry Anggara (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The largest production of paddy is produced from rain-fed rice fields scattered in Kecamatan Pulau Laut Timur. With the Operation and Maintenance on rainfed rice field is expected to improve service to local farmers. To evaluate the Operation and Maintenance can be measured by measuring its dimensions in the form of: 1) Facility / physical infrastructure, 2) Supporting facilities, 3) Organization, 4) Documentation, institutional condition, and 5) Productivity cropping. This study aims to determine the level of farmers' perceptions of Operation and Maintenance activities, then provide recommendations for priority development and improvement of Operation and Maintenance management. By using quiz dispersion method for farmer perception and expectation in Kecamatan Pulau Laut Timur. The data were processed by quantitative descriptive analysis, TKi suitability analysis, quadrant analysis to determine the priority order of the improvement of OP. The result of the analysis of the farmers' suitability level was in the dissatisfied category, with the percentage of TKi ≤ 100%. And quadrant analysis: the main improvement priority in quadrant I (one), that is in the low priority, the variable is in (X1,1), where the channel condition is not in line with the farmer's expectation. Evaluation and development of rainfed maintenance and maintenance operations by raising awareness of farmers maintaining and maintaining channels. The need for technical / non-technical irrigation infrastructure development to support the success of agricultural activities. Keywords : Farmers perception, Irigations, Operation and maintenance, Rainfed rice field